2014
DOI: 10.4103/2230-8598.137706
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficacy of Widal slide agglutination test against Widal tube agglutination test in enteric fever

Abstract: Introduction: Enteric fever is an endemic disease in India and warrants rapid and affordable diagnosis. The Widal slide agglutination test is a commonly used rapid screening test for this purpose. The literature available on its diagnostic ability in comparison to the tube agglutination test is however scanty. Hence, this study aims to evaluate the effi cacy of the Widal slide agglutination test and the tube agglutination test for the diagnosis of enteric fever. Materials and Methods: A total of 1470 sera were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Similar results of high false positivity and low PPV of slide agglutination (65.5% and 28.9% respectively) were also detected in various earlier done studies. 1,8 This clearly proves that, although the slide agglutination test is useful in screening out negative samples, the positivity expressed by it is not always helpful in diagnosing the disease correctly. The high false positivity exhibited by slide agglutination in the present study could be attributed to the endemicity of the disease in our region and possible presence of cross reacting antibodies of other bacterial and non-bacterial infections.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Similar results of high false positivity and low PPV of slide agglutination (65.5% and 28.9% respectively) were also detected in various earlier done studies. 1,8 This clearly proves that, although the slide agglutination test is useful in screening out negative samples, the positivity expressed by it is not always helpful in diagnosing the disease correctly. The high false positivity exhibited by slide agglutination in the present study could be attributed to the endemicity of the disease in our region and possible presence of cross reacting antibodies of other bacterial and non-bacterial infections.…”
Section: Discussionmentioning
confidence: 97%
“…This is found to be similar to another study which showed sensitivity and specificity of slide test to be 100% and 84.9% respectively. 8 Another study showed sensitivity and specificity of slide test to be 53-80% and 57-90% respectively. 16 It has been found that the positive predictive value (PPV) is the most important measure of a clinical diagnostic method since it represents the proportion of patients with positive test results that are correctly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations